2018
DOI: 10.1038/s41388-018-0446-2
|View full text |Cite
|
Sign up to set email alerts
|

IITZ-01, a novel potent lysosomotropic autophagy inhibitor, has single-agent antitumor efficacy in triple-negative breast cancer in vitro and in vivo

Abstract: Autophagy is a homeostatic process that recycles damaged organelles and long-lived proteins by delivering them in double-membrane vesicles to lysosomes for degradation. Autophagy has a prominent role in survival, proliferation, and resistance of tumors in metabolic and chemotherapeutic stress conditions. Clinical trials with chloroquine-a known autophagy inhibitor-were unable to achieve complete autophagy inhibition in vivo, warranting the search for more potent autophagy inhibitors. In a process of exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 56 publications
0
31
0
2
Order By: Relevance
“…Moreover, clinical trials showed that autophagy is unable to be completely inhibited by CQ in vivo. These warrant us that searching more potent autophagy inhibitors is critical for promoting an opportunity to apply the combination therapeutic strategy in clinical studies (Lalita Guntuku et al, 2019), especially agents that specifically inhibit autophagyrelated (ATG) proteins (Pei-Feng Liu1 et al, 2018).…”
Section: The Challenge and Development Of Targeting Cytoprotective Aumentioning
confidence: 99%
“…Moreover, clinical trials showed that autophagy is unable to be completely inhibited by CQ in vivo. These warrant us that searching more potent autophagy inhibitors is critical for promoting an opportunity to apply the combination therapeutic strategy in clinical studies (Lalita Guntuku et al, 2019), especially agents that specifically inhibit autophagyrelated (ATG) proteins (Pei-Feng Liu1 et al, 2018).…”
Section: The Challenge and Development Of Targeting Cytoprotective Aumentioning
confidence: 99%
“…IITZ-01 exerts an anticancer effect in breast, colon and prostate cancer cells [ 15 , 16 ]. We examined whether IITZ-01 could augment TRAIL-induced apoptosis in human renal carcinoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…IITZ-01, a novel potent lysosomotropic autophagy inhibitor, induced vacuolated appearance of cells due to deacidify lysosomes. IITZ-01 showed more than 10-fold potent autophagy inhibition compare with chloroquine [ 16 ]. As shown in Figure 1 b, IITZ-01 also induced vacuolation in renal carcinoma Caki-1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations